2004
DOI: 10.1158/1078-0432.ccr-03-0731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Identification of Subgroups of Grade III Invasive Ductal Breast Carcinomas with Different Clinical Outcomes

Abstract: Tumor grade is an established indicator of breast cancer outcome, although considerable heterogeneity exists even within-grade. Around 25% of grade III invasive ductal breast carcinomas are associated with a "basal" phenotype, and these tumors are reported to be a distinct subgroup. We have investigated whether this group of breast cancers has a distinguishing pattern of genetic alterations and which of these may relate to the different clinical outcome of these patients. We performed comparative genomic hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 30 publications
6
126
0
Order By: Relevance
“…Out of these cases, 10 showed expression of basal/myoepithelial markers (ie, Ck5/6, Ck14, Ck17 and EGFR). 19,21,26,27,30,31 Although NGFR showed no prognostic significance in this cohort, when its expression was analysed in a cohort of 37 basal-like breast carcinomas, 26 NGFR showed a statistically significant association with lack of lymph node metastasis. In addition, initial analysis in 37 basal-like breast carcinomas has revealed statistically significant associations between NGFR expression and longer disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Out of these cases, 10 showed expression of basal/myoepithelial markers (ie, Ck5/6, Ck14, Ck17 and EGFR). 19,21,26,27,30,31 Although NGFR showed no prognostic significance in this cohort, when its expression was analysed in a cohort of 37 basal-like breast carcinomas, 26 NGFR showed a statistically significant association with lack of lymph node metastasis. In addition, initial analysis in 37 basal-like breast carcinomas has revealed statistically significant associations between NGFR expression and longer disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, recent data from our laboratory have suggested that basal tumours are heterogenous in terms of their molecular genetic profiles and that there might be a subgroup with a more favourable prognosis. 31 We hypothesised that, as NGFR is consistently expressed by myoepithelial cells of the breast, 5 it would also be expressed by a subset of basal-like breast carcinomas. Furthermore, given that NGFR may block tumourigenesis and induce apoptosis in some systems, it seemed possible that basal-like breast carcinomas with NGFR expression would have a more favourable prognosis compared to NGFR-negative basal-like breast carcinomas.…”
mentioning
confidence: 99%
“…[90][91][92][93][94] This may be in part due to the presence of a dysfunctional BRCA1 pathway in these tumors. 32,82,83 BRCA1 gene promoter is methylated in 460% of medullary 95,96 and metaplastic 32 breast cancers of basal-like phenotype.…”
Section: S Badve Et Almentioning
confidence: 99%
“…1 At diagnosis, approximately 70-80% of breast carcinoma are positive for estrogen receptors (ERs) and/or progesterone receptors (PgRs), and B20% overexpress Her-2/neu. [2][3][4] These findings could be related with gene expression-profiling studies, [5][6][7][8][9][10][11][12][13][14] which identify diverse varieties of breast carcinoma, mainly the 'luminal' one associated with hormone receptors, the 'Her-2/ neu-positive' and the 'basal' or 'triple negative' breast carcinoma (negative for ERs, PgRs and Her-2/neu).…”
mentioning
confidence: 99%